The mountaineering expedition as a mental health support metaphor for european high-performance athletes - Devoto, M.; Spolverato, L.; Bertran-Gracia, L.; Kinnafick, F.; Kenttä, G.; Kegelaers, J.; Jordana, A.; Ruffault, A.; Raedts, E.; Regüela, S.; De Brandt, K.; Wylleman, P.; et al. (Journal of Clinical Sport Psychology, 2026)
We describe a clinical, evidence-based metaphor of a mountaineering expedition to assist mental health professionals in supporting and caring for the mental health of high-performance athletes. Our work is based on a qualitative analysis of responses to open-ended questions provided to 318 elite athletes in six European countries: Belgium, France, the Netherlands, Spain, Sweden, and the United Kingdom. Our mountaineering expedition metaphor, which we outline in terms of practical strategies to adopt as part of interventions to foster mental health, encompasses six interrelated themes that reflect key mental health support components: (a) preparing the expedition, (b) packing the backpack, (c) setting up base camp, (d) turning on the walkie-talkie, (e) attacking the summit, and (f) debriefing. The mountaineering expedition metaphor provides practical and transferable language to facilitate discussion, reduce stigma, and improve mental health literacy. Practitioners are invited to explore metaphor-based approaches to supporting mental health.